Gender in the Middle East and North Africa : Progress and Remaining Challenges - Vishwanath, Tara; Krishnan, Nandini (World Bank, Washington, DC, 2012)
The Middle East and North Africa (MENA) region has made impressive strides in reducing gender gaps in human development. The ratio of girls to boys in primary and secondary education is 0.96, women in the region are more likely than men to attend university, maternal mortality is around 200 deaths per 100,000 live births (compared to a world average of 400 deaths), and fertility rates have decreased in the past decade. Although gender gaps in school completion rates still exist in some MENA countries, most countries are well on their way to achieving gender parity in key human development indicators.